1999
DOI: 10.1002/(sici)1097-458x(199906)37:6<421::aid-mrc479>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

GIAO-DFT prediction of accurate NMR parameters in selected glucose derivatives

Abstract: Multinuclear magnetic resonance isotropic nuclear shieldings and their principal components for α‐ and β‐glucose and several related compounds were calculated at the DFT/6–31+G* level of theory using the B3PW91 density functional. The absolute values were converted to chemical shifts and compared with experiment. A good performance of the DFT method in the prediction of the GIAO NMR parameters for simple sugars was observed. The corresponding RHF results yielded significantly lower agreement with available exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 28 publications
4
32
0
Order By: Relevance
“…Recently, DFT NMR calculations using Gauge-Invariant Atomic Orbitals (GIAO) model have became popular [28] and have been shown to successfully predict accurate chemical shifts (d, ppm) for small isolated molecules [22,[29][30][31][32]. While some studies seem to favor DFT predictions over the RHF method [31,32] the accuracy of NMR theoretical predictions most strongly depends on the implemented basis set and the optimized structural parameters.…”
Section: Simulated Nmr Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, DFT NMR calculations using Gauge-Invariant Atomic Orbitals (GIAO) model have became popular [28] and have been shown to successfully predict accurate chemical shifts (d, ppm) for small isolated molecules [22,[29][30][31][32]. While some studies seem to favor DFT predictions over the RHF method [31,32] the accuracy of NMR theoretical predictions most strongly depends on the implemented basis set and the optimized structural parameters.…”
Section: Simulated Nmr Spectramentioning
confidence: 99%
“…While some studies seem to favor DFT predictions over the RHF method [31,32] the accuracy of NMR theoretical predictions most strongly depends on the implemented basis set and the optimized structural parameters. Here the simulated spectra where calculated using the B3LYP/6-31G(d) structural parameters for conformer 1.…”
Section: Simulated Nmr Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Similar procedures were used by Kupka et al, [31] where GIAO DFT calculations of glucose derivatives were performed on MM+ optimized structures with satisfactory accuracy of predicted NMR parameters. Forsyth and Sebaga [32] compared the calculated chemical shifts of many different compounds using both ab initio and molecular mechanics (MM3)-optimized structures as inputs for GIAO DFT calculations followed by empirical scaling of thus obtained shielding constants.…”
Section: Conformational Analysis Of Gentiobiose 157mentioning
confidence: 99%
“…The application of density functional theory (DFT) has been especially useful for large organic molecules or molecules with transition metal atoms [30][31][32][33]. Among methods employed to calculate the NMR parameters such as CSGT, IGLO, GIAO and IGAIM, the GIAO method shows the best basis-set convergence and is employed by most quantum chemistry programs capable of computing nuclear shielding [30,34]. A number of applications have shown that the GIAO-DFT method is capable of reproducing experimental values for chemical shifts of transition metal complexes.…”
Section: P Chemical Shiftsmentioning
confidence: 99%